Suppression of Midgut Microbiota Impact Pyrethroid Susceptibility in Aedes aegypti - Gómez-Govea, Mayra A.; Ramírez-Ahuja, María de Lourdes; Contreras-Perera, Yamili; Jiménez-Camacho, Armando J.; Ruiz-Ayma, Gabriel; Villanueva-Segura, Olga Karina; Trujillo-Rodríguez, Gerardo de Jesús; Delgado-Enciso, Iván; Martínez-Fierro, Margarita L.; Manrique-Saide, Pablo; Puerta-Guardo, Henry; Flores-Suárez, Adriana E.; et al. (Frontiers in Microbiology, 2022)
Aedes aegypti is the mosquito that transmits viral diseases such as dengue, chikungunya, Zika and yellow fever. The insect’s microbiota is recognized for its role in the regulation of several biological processes including digestion, metabolism, egg production, development, and immune response. However, the role of these bacteria in insecticide susceptibility has not been established. Therefore, the objective of this study was to characterize the resident microbiota in a field population of Ae. aegypti to evaluate its role associated with the susceptibility to the insecticides; permethrin and deltamethrin. Mosquitoes were fed with 10% sucrose mixed with antibiotics, and then exposed to insecticides using a diagnostic dose. DNA was extracted, and sequencing of bacterial 16S rRNA was carried out on Illumina® MiSeq™. Our results showed Proteobacteria (92.4%) and Bacteroidetes (7.6%) as natural residents. When the microbiota was modified, we observed a decrease in survival of mosquitoes exposed to permethrin and an increase in survival when exposed to deltamethrin. The most abundant bacteria species after exposure to permethrin were Pantoea agglomerans (38.4%), Pseudomonas azotoformans-fluorescens-synxantha (14.2%) Elizabethkingia meningoseptica (38.4%) and Ps. azotoformans-fluorescens-synxantha (26.1%) were the most abundant after exposure to deltamethrin. We found that the modification of the microbiota modifies the response of mosquitoes to permethrin. These results are important for a better understanding of mosquito physiology in response to insecticides.